Design and Implementation of a Digital Bracelet to Regulate the Rhythm of the Heart - Urbina Avila Gustavo Amiel; Colín Jiménez Silvia Guadalupe; Gutiérrez Herrera Pablo; Marrón Noé Domingo; Caballero Alfaro Arístides; Mendoza Montero Fátima Y.; Avila Pérez Tagle Alfonso (European Scientific Journal, ESJ, 2018)
The aim of this present study is to help people suffering from cardiovascular diseases by designing and implementing a digital bracelet that allows keeping a record of cardiac behavior to generate a more optimal diagnosis of the patient's current state and the evolution of the heart rate of the same patient. The research used the evolutionary methodology. This methodology consisted of three stages: specification, development, and validation. In this study, 95% reliability was used. The results obtained with the present study were favorable. In addition, the digital bracelet has an important acceptance both in the patients and in the doctors who attended the people with cardiovascular disease.